ENVIRONMENTAL CONSEQUENCES OF COMBAT ACTIONS ON THE TERRITORY OF UKRAINE: MONITORING THE IMPACT OF FIRE - Ulyhanets, Serhii; Syrovets, Serhii; Melnyk, Liudmyla; Dovhan, Nataliia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . War is always accompanied by destruction, suffering, and profound socio-economic upheavals. However, one of the least visible yet no less significant areas of its impact is the environment. Combat actions on the territory of Ukraine have caused large-scale environmental problems that have long-term effects on natural ecosystems, public health, and the overall ecological balance of the region. This article examines the major environmental consequences of combat actions in Ukraine, their impact on the natural environment, and ways to minimize the damage. M e t h o d s . The study utilized general scientific and specialized research methods, including analysis and synthesis, and logical constructions to formulate the theoretical and methodological foundations of the investigation into the environmental consequences of combat actions in Ukraine and the country’s ecological resilience under various aspects of warfare. Expeditionary and remote methods were employed to collect initial data, such as surveys of forest fire-affected areas. Geospatial analysis methods were applied in processing the data and conducting further analysis, enabling the creation of thematic maps to structure information on forest fires in particularly valuable territories of the nature reserve fund. Geospatial modeling and cartographic methods were used to analyze materials on the impact of military aggression on Ukraine. This combination of methods provides a comprehensive understanding of the war’s environmental consequences and aids in developing effective strategies for mitigation. R e s u l t s . Research findings indicate that employing fire as a weapon in combat operations results in significant environmental and social losses. Overcoming these consequences requires long-term programs for restoring the natural environment, cleaning contaminated zones, and mobilizing international resources and technologies. A proposed methodological model for assessing the impact of war-induced fires in Ukraine includes monitoring affected areas, cleaning contaminated zones, restoring forests and ecosystems, and securing international support for rehabilitating the ecological balance. C o n c l u s i o n s . The use of fire as a weapon during combat actions in Ukraine has triggered a severe environmental crisis. Minimizing the damage and restoring ecological balance require the implementation of comprehensive long-term programs involving both national efforts and international support.